Building Patient Loyalty: The Role of Brand Image and Service Quality in Outpatient Healthcare Revisit Behavior-A Systematic Review - Rosyida, Hindun Luthfia; Suprapto, Sentot Imam; Agusta Dian; Indasah (Chakra Brahmanda Lentera Institute, 2025)
Background: In the competitive outpatient healthcare sector, clinics struggle to retain and attract returning patients. Brand image and service quality significantly influence patient satisfaction and revisit decisions. A strong reputation and high service standards are expected to enhance loyalty and revisit rates. However, their interaction in hospital settings remains underexplored. This systematic review examines how brand image and service quality affect patient return behavior, satisfaction, and loyalty in outpatient clinics. Methods: A systematic review following the PRISMA approach was conducted on studies published between 2020 and 2024. The review included research assessing the impact of brand image and service quality on patient satisfaction and revisiting intentions. Using a structured selection process, relevant studies were identified from academic databases. The analysis focused on cross-sectional, case study, and survey-based research to determine key factors influencing patient revisit behavior in outpatient healthcare settings. Results: The review found that brand image and service quality significantly impact patient revisit behavior. A strong brand image was consistently linked to higher patient loyalty and revisit intentions. High service quality, characterized by timely service, professionalism, and responsiveness, emerged as a crucial determinant of patient satisfaction and return behavior. Several studies emphasized service quality as an essential factor in shaping positive patient experiences. Additionally, the relationship between brand image and service quality was interdependent, with each factor reinforcing the other. Conclusion: This review highlights the critical roles of brand image and service quality in influencing patient revisit behavior in outpatient healthcare services. To enhance patient retention, healthcare facilities should strengthen their brand image through effective communication and improving service quality to meet patient expectations. Future research should investigate longitudinal effects and patient segmentation to understand further the dynamics of patient revisit behavior in healthcare settings.